2015
DOI: 10.1159/000369978
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Antipsychotic Drugs in Anorexia Nervosa: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Second-generation antipsychotic drugs (SGAs) are increasingly administered to achieve weight gain in anorexia nervosa. In this meta-analysis, we aimed to determine if any evidence for this treatment option can be derived from randomized controlled trials (RCTs). Methods: Based on the ‘World Federation of Societies of Biological Psychiatry (WFSBP) Guidelines for the Pharmacological Treatment of Eating Disorders', a systematic update literature search was applied to identify all RCTs investigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 36 publications
0
54
0
6
Order By: Relevance
“…Interest in pharmacological approaches is starting to increase, as summarised in a recent review [129]. There is mixed evidence for the use of antipsychotic medications to treat AN [130], although a recent multicenter outpatient study of olanzapine found small positive effects on agitation and weight gain (albeit with no difference in rates of hospitalisation) [131]. The field may need to consider using drugs that have been shown to have benefit in OCD.…”
Section: Treatment-resistant Depression and Other Co-morbidities As Mmentioning
confidence: 99%
“…Interest in pharmacological approaches is starting to increase, as summarised in a recent review [129]. There is mixed evidence for the use of antipsychotic medications to treat AN [130], although a recent multicenter outpatient study of olanzapine found small positive effects on agitation and weight gain (albeit with no difference in rates of hospitalisation) [131]. The field may need to consider using drugs that have been shown to have benefit in OCD.…”
Section: Treatment-resistant Depression and Other Co-morbidities As Mmentioning
confidence: 99%
“…The atypical antipsychotic olanzapine, an antagonist at serotonin and dopamine receptors, is of interest as a treatment option for AN [26][27][28][29][30][31]113]. It has been reported to lead to weight gain in patients with schizophrenia [114] on the basis of its high affinity towards the histaminergic H1 receptor and its antihistaminergic action [115].…”
Section: Neural Circuits and Neurotransmittersmentioning
confidence: 99%
“…According to the mentioned current review to identify recent developments in the pharmacotherapy of eating disorders [30] and a recent meta-analysis [113], olanzapine is the most promising drug for patients with AN, because with regard to weight gain it was superior to placebo in four published RCTs [26][27][28][29], and in a not yet published but recently completed large, multisite RCT in patients with anorexia nervosa performed by Attia et al [30]. In these studies, body weight gain was the major outcome measure.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…There is no evidence that selective serotonin reuptake inhibitors (SSRIs), tricyclic antidepressants, or antipsychotics are effective in treating AN 49,50. However, a Cochrane review in 2003 found that antidepressant agents were effective for the treatment of BN compared to placebo 51.…”
Section: Management Of the Triadmentioning
confidence: 99%